Persepsi Guru Teknik Ketenagalistrikan terhadap Penerapan Kurikulum Merdeka di Sekolah Menengah Kejuruan - Ariffun, Ariffun; Effendi, Hansi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This research aims to determine the perceptions of electrical engineering teachers regarding implementing the independent curriculum at SMK Negeri 1 Bukittinggi. This research was conducted using a qualitative approach with descriptive methods. Data collection techniques were carried out using interviews, observation, and documentation. In testing the validity of the data, researchers used the triangulation technique method. Data analysis techniques use data reduction, data presentation, and conclusions. Based on the results of research that has been carried out, it show that the concept of independent learning that has been implemented at SMK Negeri 1 Bukittinggi, especially electrical engineering teachers, is suitable for the current rapidly developing technological era. This curriculum adapts to the situation and needs of students as well as the conditions of each school. Its application facilitates the teaching and learning process. Each learning topic can be understood better. This research suggests that improving facilities and resources that support the independent curriculum policy, such as learning aids, teaching materials, and educational technology, is very important to ensure the curriculum can run optimally. It is necessary to carry out regular evaluations of the independence climate to ensure that the changes implemented truly improve the quality of education. Organize more online and offline training and workshops for teachers regarding the independent curriculum.